Patterns of PCR Amplification Artifacts of the Fungal Barcode Marker in a Hybrid Mushroom - Zhou, Jun-Liang; Xu, Jianping; Jiao, An-Guo; Yang, Li; Chen, Jie; Callac, Philippe; Liu, Yu; Wang, Shou-Xian (Frontiers in Microbiology, 2019)
The polymerase chain reaction is widely used in modern biology and medicine. However, PCR artifacts can complicate the interpretation of PCR-based results. The internal transcribed spacer (ITS) region of the ribosomal RNA gene cluster is the consensus fungal barcode marker and suspected PCR artifacts have been reported in many studies, especially for the analyses of environmental fungal samples. At present, the patterns of PCR artifacts in the whole fungal ITS region (ITS1+5.8S+ITS2) are not known. In this study, we analyzed the error rates of PCR at three template complexity levels using the divergent copies of ITS from the mushroom Agaricus subrufescens. Our results showed that PCR using the Phusion® High-Fidelity DNA Polymerase has a per nucleotide error rate of about 4 × 10–6 per replication. Among the detected mutations, transitions were much more frequent than transversions, insertions and deletions. When divergent alleles were mixed as templates in the same reaction, a significant proportion (~30%) of recombinant molecules were detected. The in vitro mixed-template results were comparable to those obtained from using the genomic DNA of the original mushroom specimen as template. Our results indicate that caution should be in place when interpreting ITS sequences from individual fungal specimens, especially those containing divergent ITS copies. Similar results could also happen to PCR-based analyses of other multicopy DNA fragments as well as single-copy DNA sequences with divergent alleles in diploid organisms.